New Approaches to Anticipate the Risk of Reverse Zoonosis - Jia, Peng; Dai, Shaoqing; Wu, Tong; Yang, Shujuan (Trends in ecology & evolution (Amsterdam), 2021)
The coronavirus disease 2019 (COVID-19) pandemic can cause reverse zoonoses (i.e., human–animal transmission of COVID-19). It is vital to utilize up-to-date methods to improve the control, management, and prevention of reverse zoonoses. Awareness of reverse zoonoses should be raised at both individual and regional/national levels for better protection of both humans and animals.